Pengaruh Emotional Marketing dan Perceived Ease of Use terhadap Donation Intention melalui Digital Payment - Siti Nurjannah; Suryana Hendrawan (SAFE-Network, 2023)
LAZISMU is one of the zakat institutions that manages donations from all over Indonesia and implements donations through digital payments. This study aims to examine how Emotional marketing and Perceived ease of use affect Donation intention through Digital payment at LAZISMU. This study uses a quantitative method with data collection using the Likert scale method and primary data from respondents collected by distributing questionnaires to respondents via google form. The population of this study are donors who intend to make donations at LAZISMU Yogyakarta area through digital payment. Using purposive sampling method, this study used 100 donors as a sample of respondents. Data analysis techniques through the IBM SPSS statistical 26 programme using the Coefficient of Determination test, multiple regression test and hypothesis testing. The results of this study indicate that first, Emotional marketing has a positive and significant effect on donation intention with a coefficient value of 0.115 and a significance of 0.010 which is smaller than 0.05. Second, Perceived ease of use is proven to have an effect on donation intention at LAZISMU, as evidenced by the coefficient value of 0.565 and a significance of 0.000 which is smaller than 0.05 and this study emotional marketing and Perceived ease of use, are able to explain 49.7% of the influence on the dependent variable, namely donation intention. So from the results of multiple regression tests and hypothesis testing it can be seen that the results of this study indicate that emotional marketing and Perceived ease of use have a significant effect on donation intention.